2018
DOI: 10.1111/jvim.15306
|View full text |Cite
|
Sign up to set email alerts
|

Demographic risk factors for lymphoma in Australian dogs: 6201 cases

Abstract: BackgroundLymphoma is common in the dog. Studies of population risk factors primarily have been derived from referral institution or insurance data.ObjectiveTo identify and quantify the host risk factors for lymphoma in a broad population of Australian dogs.AnimalsData on 6201 client owned dogs were retrieved from a commercial veterinary laboratory, a general practice group and 2 referral hospitals.MethodsData collected included breed, sex, and neuter status. A reference population of 640 105 dogs was generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
4
15
2
1
Order By: Relevance
“…Female dogs had twice the odds of being reported as affected by lymphoma than male dogs in this study, which was in contrast to previous findings across multiple breeds that females, 25 and particularly intact females, had a decreased risk 21 , although there may be some breed variation for sex predisposition. 25 Furthermore, the common practice of desexing in Australia most likely explains the small number of entire dogs in this study, making interpretation of this information difficult. In people, being female and the use of hormone therapy with oestrogen and/or progestin have been associated with a decreased risk of non-Hodgkin's lymphoma, 45,46 although another study did not show the same relationship.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Female dogs had twice the odds of being reported as affected by lymphoma than male dogs in this study, which was in contrast to previous findings across multiple breeds that females, 25 and particularly intact females, had a decreased risk 21 , although there may be some breed variation for sex predisposition. 25 Furthermore, the common practice of desexing in Australia most likely explains the small number of entire dogs in this study, making interpretation of this information difficult. In people, being female and the use of hormone therapy with oestrogen and/or progestin have been associated with a decreased risk of non-Hodgkin's lymphoma, 45,46 although another study did not show the same relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…The analyses performed provided evidence that there is familial clustering in affected ABCs, consistent with conclusions from epidemiological studies that a genetic predisposition for canine lymphoma is present in ABCs. 22,25 The mean age of diagnosis in this study was 9 years and was comparable to that of previous non-breed-specific studies, which reported a mean range of diagnosis from 6.7 to 8.3 years. 13,19,20,40,41 The peak age for developing lymphoma in this study was 7-11 years, which is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations